2021
DOI: 10.1057/s41262-020-00228-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of value perceptions on purchase intention of sustainable luxury brands in China and the UK

Abstract: Despite luxury brands' efforts to incorporate sustainable development into their branding and product design, studies have shown inconclusive evidence about consumers' reaction towards such efforts. This study investigates how consumption values (i.e. the need for exclusivity, conformity, and hedonism) affect consumers' acceptance of luxury brands' sustainable efforts. It adopts a cross-cultural framework by analysing two countries, namely China and the UK, which differ substantially in some of Hofstede's cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 97 publications
(159 reference statements)
3
51
0
1
Order By: Relevance
“…The investigated account posts were found to have caused emotions of happiness and joy amongst the followers whose comments revealed a prevalence of positive vibes. This finding is consistent with previous work that examined the positive effects of needs satisfaction on purchase intentions (see, for example, Wang et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The investigated account posts were found to have caused emotions of happiness and joy amongst the followers whose comments revealed a prevalence of positive vibes. This finding is consistent with previous work that examined the positive effects of needs satisfaction on purchase intentions (see, for example, Wang et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…COVID-19’s advent and its sweeping transformation of the political, social and economic panorama have offered a unique opportunity for scholars in every discipline to examine the “new normal” triggered by the pandemic—it signifies one of the most dramatic disruptions in contemporary marketing archives (Mahmoud, Hack-Polay, et al 2021 ; Mahmoud, Grigoriou, et al 2020 ). That could extend to the many facets of fashion brands management (Iglesias and Ind 2020 ; Wang et al 2021 ), including the brand presence on social media and the potential shift in Instagram users’ attitudes and behavioural patterns in that respect. Therefore, future research should concentrate on the investigation of how consumers’ perceptions of COVID-19 could impact the variables or moderate the relationships reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Major barriers that stop consumers from purchasing green products include structural conditions that impede sustainable behaviours and deeply embedded social and cultural norms that implicitly dictate behaviour [41]. For example, a study by Wang et al [42] indicated that most Chinese consumers implicitly perceive luxury brands with a mission of exemplarity and a duty to be socially and environmentally sustainable based on their price and promised superior quality. This reassures the belief that consumers are more likely to adopt sustainable consumption practices when the product offerings are customised to maximise consumers' utilities [43].…”
Section: Opportunitymentioning
confidence: 99%
“…To achieve favourable market appraisal, fashion merchandisers and designers should explore the potential of market demand and design environmentally friendly apparel that meet consumers' aspirations [42]. Aside from the quality requirements, eco-conscious designs and eco-friendly strategies are vital to maintaining momentum on the development of sustainable clothing.…”
Section: Opportunitymentioning
confidence: 99%
“…Thus, such cultures are more likely to indulge in symbolic luxury consumption than low-indulgence cultures. Wang et al (2021) proposed that Chinese consumers (low indulgence) may experience guilt for spending on luxury as they believe in controlling their desires, in contrast to UK consumers (high on indulgence), who exhibit a higher willingness to realise impulses. Therefore, we propose:…”
Section: Long-term Orientationmentioning
confidence: 99%